Active immunization with IL-1 displayed on virus-like particles protects from autoimmune arthritis. - Spohn, G; Keller, I; Beck, M; Grest, P; Jennings, G; Bachmann, M (2008)
IL-1 is an important mediator of inflammation and a major cause of tissue damage in rheumatoid arthritis (RA). Therapeutic administration of recombinant IL-1 receptor antagonist (IL-1Ra) is efficacious in reducing clinical symptoms of disease, but suffers from several drawbacks, including the need for frequent administrations of large amounts. Here, we show that immunization of mice with either IL-1alpha or IL-1beta chemically cross-linked to virus-like particles (VLP) of the bacteriophage Qbeta elicited a rapid and long-lasting autoantibody response. The induced Ab efficiently neutralized the binding of the respective IL-1 molecules to their receptors in vitro and their pro-inflammatory activities in vivo. In the collagen-induced arthritis model, both vaccines strongly protected mice from inflammation and degradation of bone and cartilage. Moreover, immunization with either vaccine showed superior efficacy than daily administrations of high amounts of IL-1Ra. In the T and B cell-independent collagen Ab transfer model, immunization with the IL-1beta vaccine strongly protected from arthritis, whereas immunization with the IL-1alpha vaccine had no effect. Our results suggest that active immunization with IL-1alpha, and especially IL-1beta conjugated to Qbeta VLP, might become an efficacious and cost-effective new treatment option for RA and other systemic IL-1-dependent inflammatory disorders.